096 Athlete health monitoring in paralympic athletes: a 52-week prospective study. (3rd March 2020) - Fagher, Kristina; Dahlström, Örjan; Jacobsson, Jenny; Timpka, Toomas; Lexell, Jan
Abstract : Background: Sports-related injuries and illnesses in Paralympic sport is a growing concern, but knowledge about the aetiology and risk factors is limited. Objective: To describe the annual incidence of injuries and illnesses among Paralympic athletes and to assess risk factors. Design: Prospective cohort study. Setting: Paralympic athletes Patients (or Participants): 107 Swedish Paralympic elite athletes with vision, physical and intellectual impairments, active in 19 para sports. Interventions (or assessment of risk factors): The athletes were asked to weekly report over 52 weeks the annual incidence of injuries, illnesses and quality of health in an adapted eHealth application. Main outcome measurements: Time to event, incidence rate (IR) and incidence proportion (IP) and risk factors. Results: The median number of completed weekly reports was 45 (IQR 25–52). The annual IP for injury was 68% and for illness 77%. The injury IR was 6.9/1000 hours and the illness IR 9.3/1000 hours. The median time to injury was 19 weeks (95% CI: 10.5–27.4) and to illness 9 weeks (95% CI: 1.4–16.6). Most injuries occurred during training and 34% were classified as severe (≥21 days of time loss). An increased injury risk was observed among athletes in team sports (HR 1.88; 95% CI: 1.19–2.99), athletes with a previous severe injury (HR 2.37; 95% CI: 1.47–3.83) and male athletes (HR 1.76; 95% CI: 1.06–2.93). The most common illness type was infection (84%). Athletes in team sports (HR 1.64; 95% CI: 1.05–2.54) had a higher illness risk. One third of the athletes (34%; 95% CI 32.0–35.2) reported weekly that they felt anxious/depressed and 48% (95% CI 45.7–50.1) reported moderate or extreme pain every week. Conclusions: Paralympic athletes report a considerably high incidence of injuries and illnesses as well as pain and psychological complaints. This emphasizes the need to develop preventive strategies and optimize medical services for this heterogeneous athlete population.